Determinants of Real Earnings Management in A Developing Economy: The Risk Structure and Audit Quality - Erna Fitri Komariyah; Desi Triyani; Frendy; Ulfa Rahmawati (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2021)
Firm’s risk structure and audit quality are considered as two of the most important factors which affect earnings management. Thus, this study aims to examine how the risk structure and audit quality affect real earnings management from the context of a developing economy. The risk structure in this study is classified into operational risk and financial risk which are proxied by Degree of Operating Leverage (DOL) and Degree of Financial Leverage (DFL), respectively. Audit quality is measured by Big-N audit firms clients and auditor industry specialization. This study employs the Roychowdhury real earnings management model which comprises of sales manipulation, discretionary cost reduction, and overproduction. This study’s sample is 219 firm-years of manufacturing companies listed on the Indonesia Stock Exchange between 2014 and 2016. The results show that auditor’s affiliation with Big-N audit firms are more effective than industry specialization in reducing real earnings management practices.